2013
DOI: 10.1088/1612-2011/10/4/045605
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser modification of titanium surfaces: direct imprinting of hydroxylapatite nanopowder and wettability tuning via surface microstructuring

Abstract: Femtosecond laser modification of titanium surfaces was performed to produce microstructured hydrophilic and biocompatible surface layers. Biocompatible nano/microcoatings were prepared for the first time by dry femtosecond laser imprinting of hydroxylapatite nano/micropowder onto VT6 titanium surfaces. In these experiments HAP was first deposited onto the titanium surfaces and then softly imprinted by multiple femtosecond laser pulses into the laser-melted surface metal layer. The surface relief was modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…At the incidence angle of the laser beam between 30° and 80°, the LIPSS period for metals is typically in a range of 1–4 µm [ 65 ] that agrees with the range of d for the fine periodic microgrooves observed on the micropillar/microhole walls in our study. Previously, it has been shown that the surfaces of metals and Ti-6Al-4V alloy undergo a significant femtosecond laser-induced oxidation [ 67 , 68 , 69 ]. Therefore, after laser processing of the sample, we performed an EDS examination of the elemental composition of the laser-treated surface.…”
Section: Resultsmentioning
confidence: 99%
“…At the incidence angle of the laser beam between 30° and 80°, the LIPSS period for metals is typically in a range of 1–4 µm [ 65 ] that agrees with the range of d for the fine periodic microgrooves observed on the micropillar/microhole walls in our study. Previously, it has been shown that the surfaces of metals and Ti-6Al-4V alloy undergo a significant femtosecond laser-induced oxidation [ 67 , 68 , 69 ]. Therefore, after laser processing of the sample, we performed an EDS examination of the elemental composition of the laser-treated surface.…”
Section: Resultsmentioning
confidence: 99%
“…The regimes of laser processing and the structure that is formed due to such processing have been analyzed in [11]. The structure exhibits ordered microand nanorelief, in particular, grooves that are parallel to the scanning direction.…”
Section: Resultsmentioning
confidence: 99%
“…To choose the modification regimes, we use the results of the previous work, in which we have structurally modified SMC titanium using FLR. The results of [11] show that different types of relieves can be obtained at different laser fluences and scanning rates. The modification regime with the parameters F = 0.3 J/cm 2 and = 18 μm/s is optimal with respect to biocompatibility.…”
Section: Laser Processingmentioning
confidence: 96%
“…Выбор режима модификации производился на осно-ве результатов предыдущей работы авторов по струк-турированию СМК титана фемтосекундным лазерным излучением, в которой были получены различные типы рельефа в зависимости от плотности энергии лазерного излучения и скорости сканирования [11]. Такой режим модификации с выбранными параметрами F = 0.3 J/cm ности не образуется глубоких пор и трещин, которые могут являться концентраторами напряжений, ведущих к понижению прочностных характеристик материала, особенно при циклических нагрузках.…”
Section: методика лазерной обработкиunclassified
“…Режимы лазерной обработки подробно изучены в работе [11], где и описана детально формирующаяся при такой обработке структура. Последняя представля-ет упорядоченную структуру с характерным микро-и нанорельефом, в том числе отчетливо проявляющихся бороздок, параллельных направлению сканирования.…”
Section: результаты экспериментов и их обсуждениеunclassified